The influence of digital literacy on student engagement and academic achievement - Ramadhania Novianti , Rahma; M. Suud, Fitriah (Al-Misbah (Jurnal Islamic Studies), 2025)
The development of digital technology has brought about major changes in the world of education, making digital literacy an important skill for students to adapt in the era of globalization. Students' ability to access, understand, and utilize digital information critically and ethically is believed to increase their engagement and academic achievement. This study aims to analyze the effect of digital literacy on student engagement and academic achievement at SMAIT Al-Multazam and identify the contribution of digital literacy in increasing student participation in learning and academic achievement. The method used was quantitative descriptive with a population of 118 students, data collection through Likert-scale online questionnaires, and statistical analysis using SPSS 24. The results showed that digital literacy significantly affected student engagement by 55.3% and academic achievement by 52.9%, with normally distributed data and linear relationships between variables and a statistically significant t-test. The implications of this study emphasize the importance of integrating digital literacy in the learning process to increase student engagement and academic achievement in the digital era.